Depresión y cólera-hostilidad en alumnos víctimas de violencia intrafamiliar, de cuarto grado de secundaria de instituciones educativas estatales de zonas urbano marginales de la ciudad de Lima - Huerta R., Rosa (2015)
Depression is a mood disorder prevalent in our country that increases vulnerability to suffer affective disorders in adulthood when it appears in childhood or adolescence, with clear implications for the psychosocial functioning. Furthermore anger-hostility brings negative health implications, and in many cases, predicts situations of violence, for it is seen as a result of poor emotional control. The study was subjected to the analysis of depression and anger-hostility variables according to the presence or not of domestic violence in a sample of 472 fourth high school gradestudents, victims and non-victims of domestic violence, who were given a sociodemographic data survey, the Children’s Depression Inventory and the Multicultural State-Trait Anger Expression Inventory, consisting of Wrath State (CE), Trait Anger (CR) and Expression of Anger components. It was found that there is a significant correlation between depression with each of the components of Anger-Hostility, specifically with CE, CR and Expression of anger in adolescents victims of domestic violence (sig. = 0.00). In addition, women present more depressive episodes in general, when there is domestic violence, women use to present higher depressive levels. A significant correlation between depression with CE and CR with respect to the entire sample was also found. It is the presence of domestic violence that determines and produces mental disorders in adolescent health.